Raman analysis of epitaxial GaN layers grown on Si (111) by PA MBE. (December 2020) - Lubyankina, E A; Toporov, V V; Mizerov, A M; Timoshnev, S N; Shubina, K Yu; Bairamov, B H; Bouravleuv, A D
Abstract: Epitaxial GaN layers were synthesised by PA MBE on Si (111) with and without using the high-temperature nitridation. We performed a complete investigation of their structural and optical properties. It was proven that the presence of GaN epitaxial layer less than a micrometer leads to the appearance of tensile stress in the structure. The stress was calculated and compared for the structure with nitridation and without it. The effect of nitridation on holes density was also observed by Raman spectroscopy and Hall measurements.